Epidermal growth factor-mediated activation of the unliganded glucocorticoid receptor in A549 cells - Kemp, Calvin (Department of Molecular and Cell Biology, 2025)
Multiple studies have described ligand-independent glucocorticoid receptor (GR) activation in which non-steroidal ligands are able to activate the GR in the absence of glucocorticoids. This study investigates the regulatory effects of epidermal growth factor (EGF) on cytokine gene expression in order to determine whether previously published examples of EGF repressing the expression of interleukin 6 (IL-6) mRNA occur in other cell types and whether the effects of EGF are mediated via the GR. This study provides the first evidence of a single ligand (EGF) causing ligand-independent GR activation, resulting in the regulation of cytokine genes in the lung epithelium fibroblast A549 cell line. Evidence suggests that the EGF-induced repression acts on signalling via the TLR-2 receptor but not via the protein kinase C (PKC) pathway. The EGF response is shown to act via the nuclear factor kappa B (NF-κB) promoter element in a GR-dependent manner. Some mechanistic insights into the regulation are provided by demonstrating that EGF results in site-specific GR phosphorylation, while EGF does not induce GR turnover or alter GR protein expression levels. A novel finding is that regulation of IL-6 mRNA expression is shown to require protein translation. Taken together, this study provides evidence that expands on the knowledge of how EGF may affect immune function and provides proof of the mechanisms likely involved.